Development of Multi-Matobe Learning Model to Prevent Radicalism in The Digital Era - Rasimin Rasimin (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Develop a multi-matobe learning model (multicultural based on the problem of religious tolerance) to ward off student radicalism. Use a Research and Development (R&D) approach with three steps, namely: 1) preliminary studies, 2) model development, and 3) model testing. The developed products were tested on UIN Salatiga, Indonesia students and analyzed by t-test using SPSS 22 software. The multi-matobe learning model uses five main syntaxes, namely: (1) determining and mapping problem priorities, (2) problem orientation, (3) social-digital investigation of religious tolerance issues, (4) group and classical discussions, and (5) presenting and developing works. The paired sample t-test showed a significant difference between the control and experimental classes in the limited-scale trial 1, limited-scale trial 2, and large-scale trial. The multicultural learning model based on the problem of religious tolerance can be used in Social Studies learning (IPS). However, applying this learning model to other subjects has a great opportunity to form a tolerant student character. The multi-matobe learning model has five syntaxes that have been tested to be effective in providing real experiences in solving religious tolerance problems. This learning model can be an alternative solution so that the younger generation is not easily exposed to radicalism in the digital era.